Formulasi dan Uji Kualitas Probiotik Berbahan Baku Lokal untuk Optimalisasi Produktivitas Usaha Ternak Unggas di Desa Salamrejo, Blitar - Kurniawan, David; Mardiana, Nur Agustin; Widigdyo, Anang; Azis, Rosidi (Universitas Pahlawan Tuanku Tambusai, 2026)
The Rojo Koyo Berkah Livestock Farmers Group in Salamrejo faces high and fluctuating commercial feed costs that reduce poultry farming profits. This program develops and applies locally sourced probiotic additives to improve productivity and promote farmer self-reliance. Using a CBAR approach, activities include four stages: needs identification, training and guided production, evaluation, and dissemination. The formulated liquid probiotic is technically and economically feasible, showing a stable pH of 3.5–4.5 and a fresh acidic aroma without contamination. Regular application in drinking water improves feed intake, digestive health, and reduces diarrhea, DOC mortality, and ammonia odor. Beyond improving poultry and duck performance, the innovation strengthens feed independence, reduces reliance on chemical inputs, and enhances group capacity through independent production. Overall, this initiative supports sustainable, community-based agricultural development at the village level.